The Learning Motivation and Learning Outcomes of Islamic Senior High School Students: Comparative and Correlative Studies between Students Who Graduate from Junior High Schools and Islamic Junior High Schools - T Idris (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
This study aims to compare the learning motivation and learning outcomes of Islamic senior high schools students who graduate from Islamic junior high schools and general junior high schools and determine the correlation between learning motivation and learning outcomes of Islamic senior high school students. This research is ex-post facto research with a quantitative approach. The data was collected using a learning motivation questionnaire and documentation of students' report scores in Mathematics, Physics, Chemistry, Biology, and English. The research sample includes 55 students who graduate from junior high schools and 155 students who graduate from Islamic junior high schools. The research results show that the students who graduate from Islamic junior high school have higher learning motivation and better learning outcomes than students who graduate from general junior high school. Furthermore, the correlation between learning motivation and learning outcomes is 0.006 and 0.038 for students who graduate from junior high schools and Islamic junior high schools, respectively. The correlation between learning motivation and learning outcomes of students who graduate from junior high school students has a smaller significance than students who graduate from Islamic junior high schools. In the future, Islamic senior high schools are expected to increase students learning motivation in an effort to improve students learning outcomes.